Prospects for recycling leather industry waste as a source of chromium-containing raw materials: physicochemical analysis of the Fe–Cr–P–O system - Stepanenko , D. O.; Togobytska , D. M.; Semiryagin , S. V.; Povorotnya , I. R.; Belkova , A. I. (Theory and Practice of Metallurgy, 2026)
The paper considers thermodynamic and physicochemical regularities of phosphorus behavior in multicomponent systems of Fe–Cr–P, Fe–Cr, Fe–P, Cr–P and Fe–Cr–P–O when using chromium-containing man-made raw materials, in particular substandard ores and leather industry wastes. The analysis of the current state of the raw material base of chromium in Ukraine is carried out and the expediency of attracting alternative sources of chromium-containing raw materials is substantiated. The literature data on phase equilibrium, thermodynamic properties and features of the formation of phosphide and oxide-phosphate phases in these systems is summarized. It has been established that the main problem of the use of man-made raw materials is the increased content of phosphorus, which negatively affects the properties of the metal. It is shown that solid-phase reduction creates favorable conditions for controlling the distribution of phosphorus between the metal and slag phases. The influence of temperature, charge composition and interatomic interaction on the stability of phosphide phases and the efficiency of dephosphorization has been determined. Particular attention is paid to the role of the magnetic state of iron and the conditions for the formation of solid solutions and intermetallics in the Fe–Cr–P system. The results obtained can be used to develop energy-efficient technologies for the processing of chromium-containing waste and substandard ores in order to reduce import dependence and increase the environmental safety of metallurgical production. The purpose of the work is to study the thermodynamic and physicochemical patterns of phosphorus behavior in the Fe–Cr–P, Fe–Cr, Fe–P, Cr–P and Fe–Cr–P–O systems when using complex chromium-containing raw materials (substandard ores and leather industry wastes), as well as to substantiate the possibility of controlled phosphorus removal in order to improve the quality of the obtained metals and alloys. Research methodology: A systematic analysis of the scientific and technical literature on phase equilibrium and thermodynamic properties of Fe–Cr–P, Fe–Cr, Fe–P, Cr–P, Fe–Cr–P–O systems was carried out. composition of the charge and reducing medium for the distribution of phosphorus between phases. Scientific novelty: The relationship between the parameters of the interatomic interaction (ZY, d, tgα, ρl) and the thermodynamic stability of phosphide phases has been established. Practical significance: The expediency of using leather industry waste as an alternative source of chromium for metallurgy has been substantiated. Approaches to reducing the phosphorus content in the processing of complex raw materials, which allows to improve the quality of steel and ferroalloys, have been proposed. The optimal temperature and thermodynamic conditions for the implementation of dephosphorization processes have been determined. The results can be used in the development of energy-efficient technologies for solid-phase recovery and recycling of waste. It helps to reduce Ukraine’s import dependence on chromium-containing raw materials and increase the environmental safety of production.